REVITALISASI NILAI-NILAI PANCASILA DALAM KONTEKS KEBHINEKAAN DAN DEMOKRASI, DAN FUNGSINYA DALAM MENCEGAH DAMPAK NEGATIF DARI ARUS GLOBALISASI DI INDONESIA - Hasugian, Andre S.B (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2024)
A contemporary issue in the life of nation and state in Indonesia today is the fading of Pancasila values. This has led to the rise of things that hurt the life of the nation and state. The issue of intolerance and division in the midst of society has become a daily news that is often heard. Not to mention the things that ruin the lives of the next generation of the nation such as pornography, drugs, and fights between students. These things can actually be prevented and do not need to happen if each of the nation's children can understand well and apply the values contained in Pancasila. Divisions can easily occur when differences are encountered. In politics leading up to the 2024 election year, sara issues are starting to be spread to the community and unfortunately this can easily create a dichotomy in the midst of these societies. Pornography is also increasingly prevalent and easy to find not only in adult societies but also in the student environment. Very young children are already familiar with what pornography is, compounded by the condition that they can very easily access these things in cyberspace. Recently, we also heard news about fights between students, and a new trend is the existence of gangster groups consisting of children in their teens that have emerged and disturbed the community in Surabaya. Seeing and reflecting on all the events above, it should be that the noble values in Pancasila are reminded and re-instilled in the midst of social life to prevent and eliminate and fortify people's lives from the negative impacts of division and polarization of groups and groups in Indonesia. The values contained in Pancasila are still relevant to stem all the negative impacts of globalization and divisions that are very likely to occur in the midst of this very plural Indonesian society. The value of Divinity will shape Indonesian society into a religious pattern of life. Human Values will make Indonesian people become human beings who can appreciate and have a social spirit and help each other. The value of Unity will create a spirit of unity and tolerance in a variety of diversity regardless of differences. People's values will provide the spirit of democracy and courtesy in politics and society in the midst of national and state life. Finally, the Value of Justice which creates a fair and equitable atmosphere for all Indonesian people regardless of their background, origin, and differences.